Conscientious Objection in Healthcare: The Requirement of Justification, the Moral Threshold, and Military Refusals - Żuradzki, Tomasz (Journal of religious ethics, 2024)
A dogma accepted in many ethical, religious, and legal frameworks is that the reasons behind conscientious objection (CO) in healthcare cannot be evaluated or judged by any institution because conscience is individual and autonomous. This paper shows that this background view is mistaken: the requirement to reveal and explain the reasons for conscientious objection in healthcare is ethically justified and legally desirable. Referring to real healthcare cases and legal regulations, this paper argues that these reasons should be evaluated either ex ante or ex post and defends novel conceptual claims that have not been analyzed in the debates on CO. First, a moral threshold requirement: CO is only justified if the reasons behind a refusal are of a moral nature and meet a certain threshold of moral importance. Second, this paper considers the rarely discussed conceptual similarities between CO in healthcare and the legal regulations concerning military refusals that place the burden of proof on conscientious objectors. This paper concludes that conscientious objection in healthcare can be accommodated only in some cases of destroying or killing human organisms.